Genetic risk score modifies the effect of APOE on risk and age onset of Alzheimer's disease. Issue 2 (12th December 2018) - Shi, Zhuqing; Yu, Hongjie; Wu, Yishuo; Ford, Madison; Perschon, Chelsea; Wang, Chihsiung; Zheng, Siqun L.; Xu, Jianfeng
Abstract : Single nucleotide polymorphism (SNP)‐based genetic risk score (GRS) and APOE genotype are both important in risk prediction of Alzheimer's disease (AD); however, the interaction between GRS and APOE has not been extensively investigated. Our objective was to determine whether GRS modifies the APOE effect on AD risk and age at onset (AAO). The study included 774 AD cases and 767 controls of European descent. Population standardized GRS was calculated based on 17 previously implicated AD risk‐associated SNPs. Association was analyzed using logistic regression, Cox proportional hazards model and Kaplan‐Meier curve. We found that GRS was significantly associated with AD risk and the association was stronger among APOE ε4 carriers. Compared to ε4 non‐carriers, the Odds Ratio (OR) for AD was 8.09 (95% Confidence Interval [CI]: 4.98‐13.63) for ε4 carriers with high‐GRS (≥1.5). In contrast, the OR was 2.55 (95% CI: 1.46‐4.49) for ε4 carriers with low‐GRS (<0.6). In conclusion, these results suggest SNP‐based GRS may supplement APOE for better assessment of inherited risk and age of onset of AD. Abstract : Individuals with APOE ε4 allele and high GRS (>1.5) carry the greatest risk (OR=8.09) of Alzheimer's disease and have the earliest onset age (median disease‐free survival age=73).